Development of portable 10 stages Marx Generator - .Kh. Eljugmani, Ahmed Saeed (2015)
High voltage equipments are often placed in open air and they are often exposed to lightning strike as well as surge voltage. They are sustaining high surge voltage during the lightning phenomena. To achieve better protection of all such power equipments and quality power supply, these voltages should be simulated and test the above said equipments in laboratories, Marx generator is the commonly used. This generator produces lightning impulse voltages of 1.2/50 μs duration. This project describes the development of a cost effective and easily portable compact 10 stages Marx Generator capable of producing lightning impulses voltage up to 25kV. In addition, three different experimental circuits of HV DC supplies have been made. The highest output was 2.5 kV DC which was taken as the main supply for the experimental and simulated Marx generator circuit. This generator can be used by small scale industries and academic institutions to demonstrate impulse voltages and also to perform testing on insulators of lower rating in laboratory. A total of 10 stages of both simulated, experimental Marx impulse generator circuit was designed and the impulse waves were recorded. The simulated recorded impulse waveform was compared with the standard impulse wave with front time of 1.2 μ seconds and tail time of 50 μ seconds. Both of circuits, the efficiency of each stages was calculated and the percentage of error in the front and tail time was also found out as well as the effects of the circuit parameters on the impulse waveform characteristics were also studied. The simulation was done with the help of Pspice Software Simulation. In this work, the comparison in terms of magnitude of the experimental and simulated 10 stages Marx generator circuit has been carried out as well as its illustrative curve has been drawn. These results have confirmed the validity of the proposed method and they were in close agreement.